Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan (Studi pada Transportasi Online GRAB, Jakarta) - Muhammad Faisal Yunas (Universitas Mohammad Husni Thamrin, 2022)
This study aims to determine: 1) the effect of service quality on customer satisfaction. 2) the effect of price on customer satisfaction. 3) the effect of service quality and price simultaneously on customer satisfaction. The type of research used in this research is quantitative research using survey methods. The sampling technique is the Nonprobability sampling method, namely the accidental sampling technique. The number of respondents is 100 people. The instrument testing technique in this research is Validity and Reliability Test, while the data analysis technique uses Multiple Linear Regression analysis, Classical Assumption Test, and Descriptive Analysis. The results showed that: 1) Service quality had a partial effect on customer satisfaction. 2) Price has a partial effect on Customer Satisfaction. 3) Service Quality and Price have a simultaneous effect on Customer Satisfaction.